The influence of grinding Bakchar iron ore on the properties of air-dried and recovered peat-ore compositions - Victor Arkhipov; Evgeniya Triphonova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The aim of the study. Bakchar iron, brown iron ores require enrichment and subsequent sintering for metallurgical processing. The peat which lies in the immediate vicinity to the ore field can serve as a binder. In metallization the peat will be the restorer and it will replace metallurgical coke. In this regard, the aim of the research is to study ore reduction effect on composition and properties of peat materials. The relevance. Owing to depletion of local iron ore base in Mountain Shoria a half the required volume of iron ore is delivered to metallurgical complexes of Kuzbass. The development of Bakchar iron ore deposits allows avoiding the costs of transporting iron ore to the steel mills of the Kuznetsk basin and the Urals from the remote mining and processing plants. Methods of the research. To obtain peat materials the authors have used Bakchar iron ore mined by hydraulic method and crushed for 0,5; 0,25 and 0,1 mm sieve. The ore was mixed with damp peat and cylindrical samples were molded. The latter were then dried and heated in an electric furnace at a speed of 5 °C per minute to 500...1100 °C in increments of 100 °C. Owing to pyrophorosity of newly restored products they were cooled in nitrogen atmosphere. Air-dried and recovered samples were tested to the limit in a drum and on the test machine MIRI-500K. In the recovered samples the authors determined the content of total, ferrous and metal iron. Test results were used to calculate the degree of recovery and plating of recovery products. Results. Ore grinding increases plastic strength of raw corporates mass. At the stage of sintering at 1100 °C ore grinding contributes to hardening of the reduced samples containing 10 % of peat to dry peat-ore mass. The conclusion. Grinding Bakchar iron ore results in some strengthening of the recovered product at high-peat thorough materials; if there is a low content of peat (10 %) ore grinding increases significantly the strength of the product at 1100 °C. The strength achieved meets the requirements of the blast furnace charging.